Customer Preferences for Using the Gojek Application: A Conjoint Analysis Study - Syafrina, Mia; Renny, Kristina (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
This research aimed to understand and determine customers' preferences for the first ride-hailing application named Gojek. Product attributes were used as independent variables, and categorized into three indicators: product quality, product features, and product design attributes. Preferences were determined by measuring utilities and importance values using the conjoint analysis method. The population of this research comprised Gojek application users in Batam, with 160 respondents determined by using a rule of thumb specified for conjoint analysis. Data were collected through an online questionnaire and processed using SPSS 22. The research results indicated that among the three indicators of product attributes, product features dominated the respondents' preferences, as evidenced by having the highest importance value, with the GoPay payment feature level being the most preferred. In second place was product quality, with data security and privacy as the preferred attributes at that level. Product design was consequently ranked last with the lowest importance value, and ease of use was the most preferred attribute.